2016
DOI: 10.1103/physrevb.93.205111
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb enhancement of superconducting pair-pair correlations in a34-filled model forκ(BEDT-TTF)2X

Abstract: We present the results of precise correlated-electron calculations on the monomer lattices of the organic charge-transfer solids κ-(BEDT-TTF)2X for 32 and 64 molecular sites. Our calculations are for band parameters corresponding to X = Cu[N(CN)2]Cl and Cu2(CN)3, which are semiconducting antiferromagnetic and quantum spin liquid, respectively, at ambient pressure. We have performed our calculations for variable electron densities ρ per BEDT-TTF molecule, with ρ ranging from 1 to 2. We find that d-wave supercon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 101 publications
(175 reference statements)
2
18
0
Order By: Relevance
“…In all lattices we find that as a function of λ,P reaches a broad peak at an intermediate value of λ before beginning to decrease. A similar broad maximum inP is seen as a function of U in zero temperature λ = 0 calculations at ρ = 0.5 [16,17]. We expect the decrease inP at larger λ and/or U is caused by the increasing effective mass of pairs.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…In all lattices we find that as a function of λ,P reaches a broad peak at an intermediate value of λ before beginning to decrease. A similar broad maximum inP is seen as a function of U in zero temperature λ = 0 calculations at ρ = 0.5 [16,17]. We expect the decrease inP at larger λ and/or U is caused by the increasing effective mass of pairs.…”
supporting
confidence: 56%
“…4) is very different from ρ = 1. At ρ ∼ 0.5 zero-temperature calculations find thatP increases with U [15][16][17]. Here, for all the lattices we find thatP increases with increasing U and λ at the same densities where T = 0 calculations find enhancement by U alone.…”
supporting
confidence: 51%
“…In addition, the existence of a dipolar spin-liquid phase has been suggested [29,30] (possibly also explaining the dielectric anomaly in κ-(ET) 2 Cu 2 (CN) 3 [31]). Furthermore, the two-orbital Hubbard model has been claimed to be relevant for the description of superconductivity in charge-transfer salts [32][33][34][35], including its proximity to charge-ordered phases [36,37]. In addition, spin and charge fluctuations near the metal-insulator transition in multiorbital models have been analyzed [38].…”
Section: Introductionmentioning
confidence: 99%
“…Pressure increases frustration, causing the spin singlets to be mobile. Calculations on an anisotropic triangular lattice [41] as well as on κ-lattices [42,57] have indeed found that superconducting pair correlations are enhanced by the Hubbard U uniquely at 1 4 -filling. DMRG calculations on a width-three triangular lattice found evidence for p-wave and d-wave SC in the density range 0.40∼0.65 [58], which would appear to agree with the conclusion from the previous work [41].…”
Section: Discussionmentioning
confidence: 93%